Exposure to sexually explicit visual media and sexual debut at age 15. (13th September 2011) - Nixon, C; Henderson, M; Wight, D; Parkes, A; Hartley, J; Hunt, K
Abstract : Background and aims: Longitudinal studies in the US have demonstrated associations between viewing sexually explicit media and early sexual initiation in adolescence. Protective effects of parental co-viewing and regulation of adolescents' media use have also been reported. To the best of the authors' knowledge, no current evidence exists on the effect of media on adolescent sexual debut. This study aimed to examine whether such associations could be demonstrated within the UK, while also examining whether access to DVD players, the internet and satellite television within adolescents' bedrooms was associated with early sex. Methods: Cross-sectional survey data was collected from 1856 pupils (mean age 15.5 years) in 13 non-denominational secondary schools in central Scotland as part of the external evaluation of Healthy Respect (www.healthy-respect.co.uk ). Multivariate logistic regression models adjusting for pupil characteristics, deprivation, media access, family processes and parental monitoring were used to examine associations between early sexual debut and (1), the viewing of sexually explicit films (UK-18 certificate), (2) general media access and (3) parental rules and co-viewing of media. Results: In multivariate analyses, for both genders, having a favourite movie that was rated with a UK-18 certificate was associated with increased risk of early sexual debut. For girls, being allowed by parents to watch sexual and/or violent media content, watching 4–5 h of television per day and having access to a DVD player in their bedroom were also associated with increased risk of early debut. No associations were found between early sexual debut and parental co-viewing of television programmes and films, however following parental rules about the content of TV programmes and films was protective for both genders. Disobeying parental rules was associated with increased risk of early sexual debut for boys only. Conclusions: These results from the UK support existing US evidence from longitudinal studies that the viewing of sexually explicit media is associated with early sexual debut and that parental monitoring of media access can have a protective effect. Although additional research is needed to determine if these UK findings can be replicated longitudinally, our results suggest that by monitoring adolescent media access and having rules about television and film viewing, parents can reduce the risk of early sexual debut. We recommend that additional research be undertaken to explore why media access and use are associated with additional risk for girls but not boys.